THE CORRECTIVE SIGNIFICANCE OF SOCIAL AND HOUSEHOLD SKILLS FORMATION IN STUDENTS WITH DOWN SYNDROME - Makmhudova Madinakhan Sobirkhonovna; Saidova Aziza; Sidiqjonova Muxlisa (Galaxy International Interdisciplinary Research Journal, 2023)
In the article, the directions of work on the formation of social and household skills of students with Down syndrome, the main goal of the formation and development of social and household skills, the formation of knowledge, skills and skills acquired by students with Down syndrome in specialized auxiliary schools and boarding schools. the information is stated.